A lumped parameter model to evaluate the relevance of excess air as a tracer of exchanged flows between transmissive and capacitive compartments of karst systems - Sivelle, Vianney; Pérotin, Laïna; Ladouche, Bernard; de Montety, Véronique; Bailly-Comte, Vincent; Champollion, Cédric; Jourde, Hervé (Frontiers in Water, 2022)
The objective of this paper is to evaluate the relevance of using excess air (EA) for the characterization of drain/matrix exchange in karst systems using a rainfall-discharge model coupled with the simulation of EA measured at the outlet of the studied system. The conceptual model assumes a linear relationship between the formation of EA and the increase of hydrostatic pressure in the capacitive part of the aquifer. The simulated EA at the spring consists of the mixing of water circulating in the different compartments of the aquifer, with their own EA signature. The analysis is performed taking as an example the Durzon karst system (Larzac, France). The modeling is applied using daily rainfall-discharge time series and 18 EA measurements at the main outlet of the karst system within 3 hydrological cycles. The main modelling results show that EA variations measured at the karst spring can be explained by recharge processes and exchange between conduit and matrix. EA measurements at the spring thus contain valuable information about the flow dynamics within the aquifer. Furthermore, results show that the use of EA measurements, despite their sparse temporal resolution, allows for reducing uncertainties in the estimation of some parameters of the reservoir model used for the simulation of karst spring discharge.